Abnormal Photoluminescence of TiO\(_2\) nanocrystals (nanoparticles and nanotube arrays) - Tai, Ly Ngoc; Hoa, Dao Thi; Hong, Le Van (Communications in Physics, 2014)
In this paper we report new abnormal photoluminescence results of TiO\(_2\) nanocrystal particles and nanotube arrays. Photoluminescence spectra were recorded for TiO\(_2\) nanocrystal particles and nanotube arrays that were synthesized by a wet chemical route and the electrochemical anodization, respectively. It was found that the TiO\(_2\) nanocrystal with small size of 5-8 nm no emitted when excited by a laser beam of 325 nm, in contrary it emitted when excited by laser beam of 442 nm. The TiO\(_2\) nanotube arrays exhibit a similar emission behavior. The nanotube arrays weakly emitted when excited by a laser beam of 325 nm and more strongly emitted when excited by a laser beam of 442 nm. The obtained results have been explained by a two-step exciting model and supposed to be related with the size effect of nanocrystal and it is an experimental evidence to believe that the TiO\(_2\) nanoparticles and nanotube arrays are applicable for photo-catalysis under sun light.